For both cross and flag : Catholic Action, anti-Catholicism, and national security politics in World War II San Francisco - Issel, William (Urban life, landscape, and policy., 2010)
Against a backdrop of war and anti-Catholic sentiment, one man loses his rights because he is falsely accused.